2018
DOI: 10.21815/jde.018.009
|View full text |Cite
|
Sign up to set email alerts
|

A Computer‐Assisted Training Approach for Performing and Charting Periodontal Examinations: A Retrospective Study

Abstract: The aim of this study was to retrospectively investigate the development of a model-based, computer-assisted training approach for performing and charting periodontal examinations in a dental clinic in Germany. The study was initiated in summer semester 2013 and repeated in two consecutive semesters (S1: 44 students, S2: 48 students, and S3: 61 students) because technical features were introduced (S2: feedback and time control; S3: input control). In each semester, new dental students who had never performed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[12][13][14] However, 2 other studies concluded that although students had a positive reaction to TEL, they still preferred the traditional learning methodology. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] All 7 studies assessed knowledge gain at level 2 (learning); however, educational tools differed among the studies. Two studies applied practical exams 13,23 ; 2 applied multiplechoice questions (MCQ), 14,15 1 applied a writing test, 12 and 2 applied educational tool combinations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[12][13][14] However, 2 other studies concluded that although students had a positive reaction to TEL, they still preferred the traditional learning methodology. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] All 7 studies assessed knowledge gain at level 2 (learning); however, educational tools differed among the studies. Two studies applied practical exams 13,23 ; 2 applied multiplechoice questions (MCQ), 14,15 1 applied a writing test, 12 and 2 applied educational tool combinations.…”
Section: Resultsmentioning
confidence: 99%
“…Within this group, 2 studies found that students favored a combination of TEL with the traditional learning methods 12‐14 . However, 2 other studies concluded that although students had a positive reaction to TEL, they still preferred the traditional learning methodology 15‐32 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forms of computerized feedback in dental simulation include visual feedback, 11 auditory feedback, 2 formative feedback, 11 tactile feedback, 12 and measure of time (chronometry) 2 . Computerized feedback has been found valuable in areas of psychomotor skill development, 2,12‐17 and also related to the development of visual skills, 18 and periodontal charting 19,20 . Some publications report the potential advantages of receiving objective, consistent and immediate computerized feedback, 11 while a study by Quinn et al.…”
Section: Introductionmentioning
confidence: 99%